Assessing the potential of wood as a green construction raw material for the circular economy of the EU and the world - Kharchenko, Viacheslav (My University, 2021)
Circular economy principles are vital for improving resilience in the supply of raw materials upon which the economy of the EU. Green raw materials are renewable, non-toxic, improve occupancy health and conserve energy and water use and waste products. Wood is an important green raw material. Wood building materials have many environmental advantages. Wood products from responsible sources are a good choice for most green building projects. Wood grows naturally using energy from the sun and CO2, is renewable, sustainable and recyclable. It is an effective insulator and uses far less energy to produce than concrete or steel.

Принципи циклічної економіки є життєво важливими для підвищення стійкості в постачанні сировини, на якій базується економіка ЄС. Екологічна сировина є відновлюваною, нетоксичною, покращує здоров’я людей і заощаджує енергію, воду та відходи. Деревина є важливою зеленою сировиною. Дерев’яні будівельні матеріали мають багато екологічних переваг. Вироби з деревини з відповідальних джерел є гарним вибором для більшості проектів зеленого будівництва. Деревина росте природним шляхом, використовуючи енергію сонця та CO2, є поновлюваною, стійкою та переробленою. Це ефективний ізолятор і споживає набагато менше енергії для виробництва, ніж бетон або сталь.
Keywords: green raw material; circular economy; wood building materials; carbon footprint; зелена сировина; циркулярна економіка; дерев'яні будівельні матеріали; вуглецевий слід; кафедра екології та екоменеджменту